Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1063/5.0039079
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of infrared emissivity by the hierarchical microstructures from the wing scales of butterfly Rapala dioetas

Abstract: Radiative cooling, which normally requires relatively high infrared (IR) emissivity, is one of the insects’ effective thermoregulatory strategies to maintain their appropriate body temperature. Recently, the physical correlation between the delicate biological microstructures and IR emissivity for thermal radiation draws increased attention. Here, a scent patch region on the hindwing of Rapala dioetas butterfly is found to exhibit enhanced IR emissivity compared with the non-scent patch regions. A series of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…All thermal effect of the possible variation of scales hierarchy in 3D is here integrally and systematically resolved for the first time. It was demonstrated that increasing the inner surface area of the lumen can enhance emissivity (Lou et al ., 2021). Naturally, all variations of scale hierarchy, surface or lateral, can influence the area of the inner surface and can conceivably influence the emissivity, but it was seldom verified how the surface parameters influence the emissivity or other optic or thermal properties (Weatherspoon et al ., 2008; Matsuoka & Monteiro, 2017, 2018; Krishna & Lee, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…All thermal effect of the possible variation of scales hierarchy in 3D is here integrally and systematically resolved for the first time. It was demonstrated that increasing the inner surface area of the lumen can enhance emissivity (Lou et al ., 2021). Naturally, all variations of scale hierarchy, surface or lateral, can influence the area of the inner surface and can conceivably influence the emissivity, but it was seldom verified how the surface parameters influence the emissivity or other optic or thermal properties (Weatherspoon et al ., 2008; Matsuoka & Monteiro, 2017, 2018; Krishna & Lee, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other traits not included in our study, such as wing iridescence (Miaoulis & Heilman, 1998), emissivity, reflectance and absorbance (Lou et al, 2021; Schmitz, 1994) or fur (modified scales) thickness (Kingsolver & Moffat, 1982) on the body, may affect heating rates and body temperatures of butterflies. Erebia butterflies are iridescent with metallic reflections in freshly hatched butterflies, which may increase absorbance of solar influx (Bosi et al, 2008) in individuals with lower wing-wear.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the fur may provide better insulation in cold conditions (Kingsolver, 1988), but it may also slow down heating. Low heating effectiveness can be caused also by different wing emissivity, reflectance and absorbance (Lou et al, 2021;Schmitz, 1994). 4.2.…”
Section: Species and Individual Effects On Thermoregulation Under Lab...mentioning
confidence: 99%
“…Compared to nonscent patch scale without living cells, Lou et al found that the scent patch scales have the similar upper chitin layer and bottom chitin layer, but an oval cavity structure forms between these two layers (Figure 5e). 47 This cavity is filled with randomly distributed microfibers and micrometer-sized pores. Optical simulation revealed that the microporous structures play the vital role in enhancing MIR emissivity.…”
Section: Triangle-shaped Microstructures For Radiativementioning
confidence: 99%
“…(f) Simulated light intensity distribution inside the scent patch. (e,f) Reproduced with permission from ref . Copyright 2021 AIP Publishing.…”
Section: Thermal Energy Regulation In Biological Systemsmentioning
confidence: 99%